Neurotechnologies and Human Talent Management: A Bibliometric Exploration, Ethical Considerations, and Future Directions - Martínez-Mora, Marco William; Mora-Cruz, Alexandra (LACCEI, 2025)
The present research develops a bibliometric review of the scientific production regarding neuroscience applications in Human Talent Management (HTM), with the purpose of identifying the most relevant trends, authors, academic sources, publishing institutions and future research lines in this area. A bibliometric review was conducted by the PRISMA methodology. A total of 35 articles from the Scopus and Web of Science databases were selected for review. The analysis was executed using Bibliométrix in R, with the objective of determining collaborative networks, sources, and thematic clusters with respect to neurosciences and HTM. The analysis identified four distinct clusters. The following topics will be covered in this study: (1) Human Talent Management; (2) Neurotechnologies in Human Talent Management; (3) AI and neurotechnologies in HTM; and (4) Neuroethics in HTM processes. In consideration of the findings, the primary research directions concerning neurotechnologies and their implementation in the domain of HTM were delineated. It is concluded that the application of neurosciences to HTM processes is an emerging and little-studied topic, however, with a promising annual growth rate. There are notable lacunae in the extant literature pertaining to neuroethics and the integration of AI and neurotechnologies with HTM processes, which point to the need for future research in these areas.